Power generation from waste of IC engines - Rahman, Mohammed Ataur; Razzak, Fadhilah; Rafia, Afroz; Mohiuddin, A. K. M.; Hawlader, Mohammad Nurul Alam (Elsevier, 2015)
Several methods for waste thermal energy recovery from internal combustion engine (ICE) have been studied by using supercharger or turbocharger and /or combined. This study presents an innovative approach on power generation from waste of IC engine based on coolant and exhaust. The waste energy harvesting system of coolant (weHSc) is used to supply hot air at temperatures in the range of 60–70 C directly into the engine cylinder, which would be useful to vaporize the fuel into the cylinder. The waste energy harvesting system of exhaust system (weHSex) has been developed with integrating fuzzy intelligent controlled Micro-Faucet emission gas recirculation (MiF-EGR) and thermoelectric generator (TEG). In this study the MiF-EGR (micro-facet exhaust gas recirculation) will be used to maintain the intake temperature 70 C by keeping flow of the exhaust to the engine cylinder chamber and to increase the engine volumetric efficiency. The TEG produces electrical power from heat flow across a temperature gradient of exhaust and delivers DC electrical power to the vehicle electrical system which could reduce the load of the alternator by as much as 10%. The performance of weHS equipped engine has been investigated by using GT suite software for optimum engine speed of 4000 rpm. The result shows that specific fuel consumption of engine has improved by 3% due to reduction of HC formation into the engine combustion chamber causes significantly improved the emission. While, the brake power has been increased by 7% due to the fuel atomization and vaporization at engine intake temperature 70 C.